The dynamic capabilities approach and regional business resilience: an Australian case study - Kathyayini Kathy Rao; Catherine Mackenzie; Sudarshan Subedi (Regional Studies, Regional Science, 2024)
The frequency and severity of major disruptions (e.g., disasters, epidemics/pandemics) are increasing, significantly impacting business survival in regional areas. Using the dynamic capabilities approach, this paper reports on the recovery pathways and resilience of Australian regional businesses during the recent COVID-19 pandemic. A case study approach is adopted to explore the capabilities through which regional businesses can plan for, recover from, and develop strategies for building resilience. Using the data from 18 semi-structured interviews with business owners operating in different industry sectors and a web-based forum with 10 key stakeholders in regional South Australia, a dynamic capabilities resilience framework is developed. Results suggest that the dynamic capabilities approach during crises can become integral to the long-term business recovery of regional Australian businesses. By revealing both the determinants of business survival and the constraints regional businesses face during major crises, the study contributes information that businesses, government and non-government agencies that support them can use to develop effective recovery pathways, which is central to the future sustainability of regional Australia.